Unmet supportive care needs of young women with breast cancer in Chile during follow-up stage after treatment: A qualitative study - Francisca Vezzani; Báltica Cabieses; Alexandra Obach; Sonia Torrealba; Iderta Carvajal (PLoS ONE, 2025)
Background Breast cancer is a significant public health issue, with a rising incidence in young women who have more aggressive tumors and a poorer prognosis. In 2022, breast cancer accounted for 20.8% of all cancers in women in Chile, highlighting the urgent need for targeted research and support for young survivors. This study aims to explore the unmet supportive care needs of these young women during their follow-up period post-treatment, addressing gaps in existing literature and healthcare responses. Methods Qualitative case study using semi-structured online interviews with 20 women who had a cancer diagnosis under 45 years of age. A thematic content analysis was conducted. Study approved by the Scientific Ethics Committee of the Universidad del Desarrollo, Chile. Results Three primary areas of concern and unmet supportive care needs were identified during follow-up period: access to information, rehabilitation and integration, and mental health. These areas are deeply interconnected, and the absence of validation of these young women’s needs leads to a lack of adequate and comprehensive support from health professionals, deepening women’s sense of abandonment by the health system. Discussion and conclusion The findings align with international literature, revealing that young women face unique challenges related to their life course. The lack of adequate support from healthcare professionals highlights the need for a multidisciplinary, person- and family-centred approach to care. It should address interlinked needs and advocate the involvement of patient organisations. This would enhance support and education regarding the needs of young women and their overall well-being during recovery process.